2005
DOI: 10.1016/j.crci.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of N-doped TiO2 particles by plasma surface modification

Abstract: A cold plasma is useful for surface modification of solid materials. In this work, plasma surface modification is tried to prepare visible-light active TiO 2 particles of which the surface is doped with nitrogen. A film composed of the particles was formed on the surface of a glass substrate by spin-casting of TiO 2 sol and then was sintered at 673 K. The film was treated with argon and nitrogen plasmas, in series. The plasma-treated film revealed visible-light absorption, in addition to ultraviolet-light abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…This confirmed the previous result that the doping N content significantly influenced the visible light activity. 25 However, no remarkable change was observed for Mo-N-TiO 2 in doping N content (2.0 and 1.88 at.% for fresh and 3rd reused catalyst), indicating that the lattice-nitrogen atoms in Mo-N-TiO 2 remained relatively stable. Devi …”
Section: +mentioning
confidence: 94%
“…This confirmed the previous result that the doping N content significantly influenced the visible light activity. 25 However, no remarkable change was observed for Mo-N-TiO 2 in doping N content (2.0 and 1.88 at.% for fresh and 3rd reused catalyst), indicating that the lattice-nitrogen atoms in Mo-N-TiO 2 remained relatively stable. Devi …”
Section: +mentioning
confidence: 94%
“…This is consistent with our previous results. 25 Yamada et al 26 prepared N doped TiO 2 by N 2 plasma method. They suggested that the scission of Ti-O bond on TiO 2 surface took place under the nitrogen plasma state, which had a high electron temperature (5-6 eV).…”
Section: Resultsmentioning
confidence: 99%
“…According to Asahi et al 3) , TiO 2-x N xˆl ms were prepared by the sputtering of TiO 2 target in N 2 (40z)/Ar gas mixture, and TiO 2-x N x powders were prepared by the treatment of anatase TiO 2 powders in NH 3 (67z)/Ar atmosphere at 873 K for 3 h. Nitrogen-doped TiO 2 powders were also prepared by the oxidative annealing of TiN powders for 90 min in an oxygen gas ‰ow at 823 K 4) . According to Irie et al 5) , TiO 2-x N x powders were prepared by the annealing of anatase TiO 2 powders under NH 3 ‰ow at 823, 848, and 873 K for 3 h. Nitrogen-doped TiO 2 particles were also prepared by a series of argon and nitrogen plasma treatment 6) . The TiO 2 particles having Ti-N bonds formed by substitutional nitrogen-doping showed photocatalytic activities under visible-light irradiation (vis irradiation).…”
Section: Introductionmentioning
confidence: 99%
“…Visible-light-active (vis-active) TiO 2 has been prepared by various methods [1][2][3][4][5][6][7][8][9] . According to Takeuchi et al 1) and Ihara et al 2) , the reduction of TiO 2 by hydrogen plasma treatment with elevated temperatures created a new absorption band in the visible-light region and showed photocatalytic activity in this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation